INVESTIGATING GRAMMAR LEARNING STRATEGY EMPLOYED BY STUDENT ENGLISH STUDY PROGRAM - Oktha Ika Rahmawati; Meiga Ratih Tirtanawati (PROJECT (Professional Journal of English Education), 2024)
The study aims to investigate grammar learning strategy used by students in grammar class. It employed a survey design as part of a quantitative research methodology. The participants were students enrolled intermediate grammar class. The instruments used was questionnaire proposed by Oxford (1990), modified by Kemp (2007) and Bayou (2015). There were 32 questions divided into six strategies. The form of response was a 5-point Likert scale, with 1 representing never and 5 representing always. The result showed that meta-cognitive and compensation were two strategies frequently employed by the students.